The management of postoperative airway after nasal endoscopic sinus surgery - Sharma, Ashish; Pyadala, Nagababu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal surgery followed by nasal packing can be vulnerable due to airway complications like, respiratory blockage and dyspnea. Thus the present study aimed to compare the nasal packing with nasal airway after the nasal surgery for the airway management. Methods: A total of 120 patients for fibreoptic endoscopic sinus surgery were included in this study. All subjects were equally divided in to 3 groups; group 1, 40 patients with traditional bilateral nasal packing; group 2, 40 patients with 5 mm internal diameter uncuffed ETT in to one of the nostrils and bilaterally in group 3 40 patients. During postoperative period all data were recorded and analyzed by using statistical analysis software 20.0. Results: In case of group 1 patients cardio-respiratory parameters reported significant variation. Pain and bleeding during removal of nasal airway and discomfort showed significant results among group 1 patients than in group 2 and group 3 patients. Conclusions: This study showed that the new intervention to manage the airway obstruction has benefits as compared to traditional nasal packing with ease of suctioning, oxygen supplementation.